2010
DOI: 10.1007/s11258-010-9722-0
|View full text |Cite
|
Sign up to set email alerts
|

Not novel, just better: competition between native and non-native plants in California grasslands that share species traits

Abstract: Invasive plants have often been shown to possess novel traits such as the ability to fix nitrogen, access unused resource pools, or the ability to exude allelopathic chemicals. We describe a case of a successful invasion where the native and non-native species are very similar in most life-history characteristics including their growth forms, lifespan, and degree of summertime activity. Data from permanent transects suggest that exotic perennial grass invaders can establish into intact native-dominated grassla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 34 publications
1
28
1
Order By: Relevance
“…While at EU sites C. stoebe biomass increased by 107%, on average, when competitors were removed, mean increase in biomass was only 18% at NA sites. Similarly to our results, Corbin and d'Antonio (2010) found that the productivity of exotic perennial grasses was not affected by the presence of native NA perennial grasses. In contrast, NA perennial grass productivity was significantly lower in plots with exotic perennial grasses, compared to plots without exotic grasses.…”
Section: R Eportssupporting
confidence: 91%
“…While at EU sites C. stoebe biomass increased by 107%, on average, when competitors were removed, mean increase in biomass was only 18% at NA sites. Similarly to our results, Corbin and d'Antonio (2010) found that the productivity of exotic perennial grasses was not affected by the presence of native NA perennial grasses. In contrast, NA perennial grass productivity was significantly lower in plots with exotic perennial grasses, compared to plots without exotic grasses.…”
Section: R Eportssupporting
confidence: 91%
“…In these settings, the length of the summer drought is shorter or is tempered by summer fog, so adult survival of bunchgrasses is likely greater, consistent with the conditions needed for coexistence that we identify here. Indeed, in these sites exotic perennial grasses are presenting a challenge to native perennial species (Corbin and D'Antonio 2010). Although the model does not explicitly address local environmental variation, it does implicitly incorporate environmental variation by combining data from a range of species and geography to estimate parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Species’ functional traits are a critical missing piece of our understanding of the scale‐dependent effects of invasion on community diversity. Invasive species have often been shown to compete most strongly with functionally similar and closely related species (Fargione, Brown & Tilman ; Strauss, Webb & Salamin ; Corbin & D'Antonio ; Brewer & Bailey ). If such limiting‐similarity competition is indeed operating, and if the species most similar to the invader are indeed the most common species in an invaded region, then a trait‐based explanation for scale‐dependent loss of diversity is supported.…”
Section: Introductionmentioning
confidence: 99%